1990
DOI: 10.2307/1966672
|View full text |Cite
|
Sign up to set email alerts
|

Fertility Conditions in Gondar, Northwestern Ethiopia: An Appraisal of Current Status

Abstract: In order to study current fertility conditions, this study examines the sociocultural, economic, and demographic characteristics of 734 women aged 15-55 in the Gondar administrative region of northwestern Ethiopia. Women over age 45 in the sample were found to have, on average, 7.27 pregnancies, 0.88 abortions, 6.39 children ever-born, 1.51 child deaths, and 4.88 live offspring. The total infertility rate was 8.5 percent, and the subfertility rate was 12.7 percent. Fertility levels in the region were relativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…In sub-Saharan Africa, the prevalence differs widely from 9% in the Gambia (Sundby et al ., 1998) and 11.8% in Ghana (Geelhoed et al ., 2002) compared with 21.2% in northwestern Ethiopia (Haile, 1990) and between 20 and 30% in Nigeria (Ebomoyi and Adetoro, 1990; Adetoro and Ebomyi, 1991; Okonofua, 1996; Larsen, 2000). Even less data are available from Asia and Latin-America, but a report compiled by the World Health Organization (WHO) indicated that the prevalence of infertility in these regions fell within the globally expected range 8–12% of couples of reproductive age and was thus lower when compared with African countries (World Health Organization, 1991).…”
Section: Prevalence Of Infertility In Developing Countriesmentioning
confidence: 96%
“…In sub-Saharan Africa, the prevalence differs widely from 9% in the Gambia (Sundby et al ., 1998) and 11.8% in Ghana (Geelhoed et al ., 2002) compared with 21.2% in northwestern Ethiopia (Haile, 1990) and between 20 and 30% in Nigeria (Ebomoyi and Adetoro, 1990; Adetoro and Ebomyi, 1991; Okonofua, 1996; Larsen, 2000). Even less data are available from Asia and Latin-America, but a report compiled by the World Health Organization (WHO) indicated that the prevalence of infertility in these regions fell within the globally expected range 8–12% of couples of reproductive age and was thus lower when compared with African countries (World Health Organization, 1991).…”
Section: Prevalence Of Infertility In Developing Countriesmentioning
confidence: 96%
“…[5] In sub-Saharan Africa, the prevalence differs widely from 9% in Gambia to 11.8% in Ghana compared with 21.2% in northwestern Ethiopia and between 20% and 30% in Nigeria. [67891011] There is paucity of data from countries of Asia to Latin America. According to the WHO, the prevalence of infertility in these regions is between 8% and 12% in couples of reproductive age.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally believed that more than 70 million couples suffer from infertility worldwide [1]. In Sub-Saharan Africa, the prevalence differs widely from 9% in the Gambia [2], 21.2% in northwestern Ethiopia [3], between 20 and 30% in Nigeria [4], [5] and 11.8% among women and 15.8% among men in Ghana [6]. There are varying opinions on the definition of infertility.…”
Section: Introductionmentioning
confidence: 99%